Stress Assessment of a Steel Bullet LPG Tank Under Differential Settlement Based on Geodetic Measurements and Sensitivity Analysis - Ferenc Tomasz; Gierasimczyk Rafał; Mikulski Tomasz (Polish Maritime Research)
This paper presents an analysis of a steel bullet LPG tank in operation at a base in Poland. The structure was set on a sand-gravel pillow and rigid concrete slab, and its settlement was periodically measured at five measuring points along the structure. After a few years, differential settlement was observed. Based on geodetic data, we attempt to assess the current stress level in the structure. The proposed methodology uses a sensitivity analysis apparatus. A numerical model of the structure and sand-gravel pillow is analysed using the finite element method, and the impact of variation in the stiffness of the sand-gravel pillow on the vertical displacement of the tank is determined. The algorithm involves six iterations of calculations, and after each iteration, the stiffness modified sand-gravel pillow is determined. After the sixth iteration, the vertical displacement in the FEM model is found to be similar to the measured values in the real structure. The results obtained after the last iteration are used to assess the stress state in the bullet tank’s shell structure.